2019
DOI: 10.1111/bdi.12730
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with the guidelines for laboratory monitoring of patients treated with lithium: A retrospective follow‐up study among ambulatory patients in the Netherlands

Abstract: Objectives Laboratory monitoring of patients using lithium is important to prevent harm and to increase effectiveness. The aim of this study is to determine compliance with the guidelines for laboratory monitoring of patients treated with lithium overall and within subgroups. Methods Patients having at least one lithium dispensing for 6 months or longer between January 2010 and December 2015 were identified retrospectively using data from the Dutch PHARMO Database Network. Laboratory monitoring was defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…Lithium remains the most effective MSA, with further evidence supporting its use in mood disorders as monotherapy and as an adjunct (Malhi et al, 2017c; Nolen et al, 2019). It is also preferable because of its additional anti-suicidal and neuroprotective properties, although it can be a little more complicated to manage and can on occasion be problematic with respect to tolerability (Malhi et al, 2012; Nederlof et al, 2019).…”
Section: Treatmentsmentioning
confidence: 99%
“…Lithium remains the most effective MSA, with further evidence supporting its use in mood disorders as monotherapy and as an adjunct (Malhi et al, 2017c; Nolen et al, 2019). It is also preferable because of its additional anti-suicidal and neuroprotective properties, although it can be a little more complicated to manage and can on occasion be problematic with respect to tolerability (Malhi et al, 2012; Nederlof et al, 2019).…”
Section: Treatmentsmentioning
confidence: 99%
“…Many studies have indicated that patients receiving lithium treatment should monitor their plasma concentration regularly throughout their life [ 47 , 48 ], but this is a burden on patients. The proportion of patients who receive regular blood lithium monitoring is often lower than the recommended standard [ 8 , 9 , 49 ]. Therefore, we can use patient information to predict whether the level of lithium treatment is sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…This approach usually takes days to weeks to reach the optimal serum concentration, which may delay the therapeutic response [ 7 ]. Moreover, in the maintenance phase of lithium therapy, the need for frequent blood draws to obtain serum levels may reduce patients’ willingness to use lithium [ 3 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in monitoring practices is needed, which is seen not only in children treated with antipsychotic drugs, but also the monitoring frequencies for adults treated in psychiatric outpatient clinics have been shown to be suboptimal according to the guidelines (25). Additionally, low monitoring frequencies are not only related to antipsychotic drug use, as low monitoring frequencies and poor adherence to clinical guidelines have also been demonstrated concerning other psychotropic drugs, including lithium, as well as somatic drugs (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%